Reflexos orçamentários em tempos de pandemia: uma análise à luz da teoria da decisão - Bevilaqua, Letícia Dibi (2022)
The consequences of the Covid-19 pandemic were extensive, especially in the years 2020 and 2021. Among them, the educational sector suspended classroom activities as a way to prevent the spread of the virus. With the premise that federal universities, which demand large amounts of public resources to develop their academic and administrative activities, had their planning shaken, this dissertation had os its main objective to analyze the impact of decisions driven by the Covid-19 pandemic in the budget execution of the Federal University of Santa Maria. As an analytical basis, the decision theory was used. The theoretical framework covered the main elements of the theoretical models of budgetary decision - Incrementalism, Serial Judgment, Multiple Streams and Punctuated Equilibrium - and the characteristics and classifications of the public budget in Brazil. This is a descriptive research of quantitative approach, documentary and case study type. Considering the years 2017 to 2021, we proceeded with the observation of the indicators of additional credits and committed expenses by expenditure sub-elements with their respective variations in the period, together with the identification of decision-making patterns according to the theoretical models. For data analysis, documentary, longitudinal, and content analysis were employed. As consequences of the Covid-19 pandemic in the budget execution at UFSM, the following main results stand out: greater flexibility in the budget through the opening of additional credits, an increase in the indicators of the expenditure nature group Investments to the detriment of Other Current Expenditures, and the possibility of meeting other demands through budget adjustments. Besides this, the budget execution was influenced by the expenses authorized by a specific extraordinary credit to face the public health emergency. The budget choices in the pandemic period fit predominantly into the pattern of the Multiple Flows model due to the period of uncertainty and unpredictability imposed by the health crisis and the high degree of ambiguity. Furthermore, the problem flow, solution flow, and political flow in the case study met the prerogatives of the model. However, characteristics of Punctuated Equilibrium were also found due to the wide variation in most expenditures when analyzed from the perspective of the detailed object of expenditure. In conclusion, the reflexes of the decisions driven by the Covid-19 pandemic on the budget execution of the UFSM stood out as the decreases in expenses with outsourced administrative, technical and operational support services and ostensible surveillance; the reduction in food supply services and food purchases; the increase in investments in ICT equipment, hospital equipment purchases and laboratory supplies to face the pandemic; increases in expenses with real estate maintenance; and higher purchases of stock materials to increase warehouse stocks.